2021
DOI: 10.1002/solr.202100762
|View full text |Cite
|
Sign up to set email alerts
|

Manipulating Grain Boundary Defects in π‐Conjugated Covalent Organic Frameworks Enabling Intrinsic Radical Generation for Photothermal Conversion

Abstract: Defects are prevalent in covalent organic frameworks (COFs) constructed based on reversible covalent chemistries. However, manipulating defects in COFs to achieve functionalities remains a significant challenge. Herein, a facial method is provided to regulate the boundary unreacted defects in π‐conjugated COFs to generate distinct and stable paramagnetic radicals, which endow the COFs with a bulk ferromagnetic transition behavior at low temperature, and the efficient photothermal conversion with application in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…[16] Recently, significant progress has been made in developing COFs for photocatalytic applications, including hydrogen and oxygen evolution reactions (HER, OER), solar-driven water splitting, CO 2 photoreduction, photodegradation of organic pollutants, photothermal conversion, and light-induced selective oxidation. [16,119,120,126] Here, we would like to shortly overview some of the recent achievements of COFs for photocatalytic applications and then provide possible ideas for future perspectives.…”
Section: Cofsmentioning
confidence: 99%
“…[16] Recently, significant progress has been made in developing COFs for photocatalytic applications, including hydrogen and oxygen evolution reactions (HER, OER), solar-driven water splitting, CO 2 photoreduction, photodegradation of organic pollutants, photothermal conversion, and light-induced selective oxidation. [16,119,120,126] Here, we would like to shortly overview some of the recent achievements of COFs for photocatalytic applications and then provide possible ideas for future perspectives.…”
Section: Cofsmentioning
confidence: 99%
“…Free radicals are the unpaired electrons on the sample, and the lower energy can make these electrons enter the excited state. Therefore, free radicals have a strong ability to absorb light with longer wavelengths and make the samples show fascinating photothermal conversion properties. ,, The surface defects and higher lattice order may limit the number of electrons entering the excited state and confine the movement of excited electrons, thereby weakening the photoacoustic coupling effect of the material and ultimately reducing the photothermal conversion capability of the sample. , At the same time, surface defects restrict photons from entering the sample, which may prevent electrons from absorbing energy and transitioning to excited states, ultimately reducing heat generation . The highly ordered carbon layer structure is not conducive to heat storage and light absorption, limiting the photothermal conversion performance of the sample .…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, Chen et al reported a strategy to manipulate the boundary defects to introduce radicals into the fully conjugated COFs while retaining their crystallinity and porous structure. [ 42 ] This will broaden the NIR absorption of the COFs for light harvesting and give rise to the efficient photothermal conversion through the nonradiative decay.…”
Section: M–z–cs Structure Design Strategies and Preparation Methodsmentioning
confidence: 99%
“…[ 21,40,41 ] In addition, the presence of paramagnetic radicals induced by boundary defects in some COF‐based composites can enhance the nonradiative relaxation of the composites, thus synergistically enhancing the photothermal conversion of the composites with the thermal vibration effect of COFs themselves. [ 42 ] Furthermore, porphyrin organic frameworks (POFs) have great potential for solar vapor generation because of their unique optical properties and their ability to grow uniformly on hydrophilic substrates with different pore sizes. Additionally, it is worth noting that POFs are a type of COFs and therefore exhibit the same photothermal conversion effect as COFs.…”
Section: Photothermal Conversion Mechanism Of M–z–csmentioning
confidence: 99%